2011
DOI: 10.1093/ejechocard/jeq187
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aortic stenosis on longitudinal myocardial deformation during exercise

Abstract: In AS, subnormal LV function can be reliably identified by 2D strain imaging at rest and during a sub-maximal exercise. That sensitive measure of LV systolic function is depressed in AS and even more in patients having the most severe AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 32 publications
(32 reference statements)
5
62
0
3
Order By: Relevance
“…At the same time, the authors observed the improvement of GLS values three months after aortic valve replacement surgery. These observations are not confirmed by Donal et al [4]. In the study by Delgado et al [6], patients with severe AS had significantly lower GLS compared to patients with hypertension with a similar degree of LV hypertrophy.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…At the same time, the authors observed the improvement of GLS values three months after aortic valve replacement surgery. These observations are not confirmed by Donal et al [4]. In the study by Delgado et al [6], patients with severe AS had significantly lower GLS compared to patients with hypertension with a similar degree of LV hypertrophy.…”
Section: Discussionmentioning
confidence: 77%
“…The usefulness of this parameter in detecting subtle changes in LV function secondary to various pathologies and their prognostic significance was shown also in AS [6][7][8]. Still little is known about the importance of exercise-induced changes in GLS in patients with high-gradient asymptomatic severe AS [4,5,9,10].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Une amélioration < −1,4 % du strain longitudinal global a été également corrélée à un risque élevé de réponse anormale à l'exercice dans le travail de Donal et al [24].…”
Section: Fonction Longitudinaleunclassified